THE FUNCTION OF THE CHRONOTOPE OF SCHOOL IN THE CONTEMPORARY NOVEL FOR CHILDREN (Heritage, 2021)
Starting from Michail Bachtin’s and Yuri Lotman’s theoretical postulates of space in an art work,the paper investigates the chronotope of school in the contemporary Serbian novel for children. The introductory part of the paper presents a review of prevailing attitudes of literary theoreticians towards space in prose works. The central part of the paper follows the function of the chronotope of school which is viewed both as the place of meetings, gatherings, conversations, bargaining, personal confessions and as the place of collision of different worlds to which protagonists belong. It reveals the mimetic and symbolic function, mostly noticeable in the characterization of the characters, the account of their mental state and social differences. The aim of the paper is to identify the function of the chronotope of school, which, having already had its mimetic function and the function of the place of the action, now becomes a certain modelling system.That system is the language for expressing spaceless categories and relationships which have a function of social criticism in a wider perspective. The corpus of investigation consists of the following novels: Miroslava Mihajlov Cerović’s Schoolyard, Vladan Zec’s The diary of one staff room, Boško Lomović’s The theft of a mobile phone in class 7 B and Dragutin Beg’s A party in school and Milutin Đuričković’s: Twins and Friday the 13th.
Keywords: chronotope, school, novel for children, symbolism, social criticism